Hawking radiation as tunneling with pressure and volume of the RN-AdS black hole - Zhi-Xuan Ren; Xiao-Xiong Zeng; Yi-Wen Han; Cheng Hu (Nuclear Physics B, 2023)
In consideration of the thermodynamic pressure and volume, we present a short and direct derivation of Hawking radiation as a tunneling process for the charged particles. Using Parikh's Semi-classical tunneling method and Lagrangian analysis on the action, we provide the geodesic equation of the massive particles via tunneling from the Anit-de Sitter (AdS) black hole. Special attention is given to calculating the imaginary part before and after particles via the horizon as the pressure and volume are considered. The result shows that the emission rates are always related to the change of Bekenstein-Hawking entropy and the exact spectrum is not precisely thermal, which are consistent with the case without pressure and volume.